Effects Of Zinc (Zn) And Chromium (Cr) On The Phenol-Degrading Bacteria Growth Kinetics - Tengku-Mazuki, T.A.; Zulkharnain, A.; Subramaniam, K.; Convey, Peter; Gomez Fuentes, Claudio German; Ahmad, Siti Aqlima (My University, 2020)
Heavy metals occur naturally within the earth crust; however, anthropogenic activities can artificially introduce these elements into the environment. Despite being the foremost isolated continent, Antarctica is not free from human contamination. Heavy metals are well-known to be the powerful inhibitors of xenobiotics biodegradation activities. A microbial growth model was presented for bacteria cell growth in the biodegradation of phenol containing heavy metals such as zinc (Zn) and chromium (Cr) ions. The Gompertz model was used to estimate three main growth parameters namely lag phase (?), maximum growth rate (μmaz), and maximum cell number at the stationary phase (Nmax). Bacterial growth for both heavy metals was shown to be properly fit towards the curve with a high value of R2 and low square root of the variance of residuals (RSME) value. The effect of heavy metals at 1.0 ppm showed that Cr has a considerable effect on bacteria consortium, inhibiting the degradation of phenol, while Zn has no effect, removing 100% of phenol. The predicted biokinetic from this model suggests the suitability of the bacteria consortium to be used in phenol removal.
Keywords: Antarctica; Degradation; Heavy Metals; Kinetic Growth; Phenol